Assessment of QT Dispersion in Prediction of Life-threatening Ventricular Arrythmias in Recipients of Implantable Cardioverter Defibrillator - Blužaitė, I.; Rickli, H.; Widmer, R.; Ammann, P.; Urbonavičienė, G.; Bertašienė, Z.; Zabiela, V. (Elektronika ir Elektrotechnika, 2007)
The aim of the study was to investigate a high risk population of an implantable cardioverter defibrillator (ICD), and to evaluate QT dispersion and its ability to predict occurrence or recurrence of life-threatening ventricular arrhythmias (ventricular tachycardia and/or ventricular fibrillation). The study population consisted of 40 unselected ICD recipients. The patients were divided in two groups: group I consisted of 16 patients with occurrence and/or recurrence of ventricular tachycardia and/or ventricular fibrillation as documented on ICD electrocardiogram, group II – 24 patients without these life-threatening arrhythmias. The groups did not differ according to the age, sex, ejection fraction, use of beta-blocking agents and cordarone. QT dispersion, evaluated at resting electrocardiogram, did not differ significantly between the groups with (58.5 + 9.3 ms) and without life-threatening ventricular arrhythmias (37.04 + 6.9 ms) in ICD recipients. The percentage of achieved workload in respect of expected one at bicycle test, had a tendency to be higher in the group II (79.4 + 7.0 %) as compared to the group I (65.0 + 4.66 %), the difference was though insignificant (p = 0.1) as well. Analysis of QT dispersion according to the diagnosis showed, that QT dispersion was significant higher in ICD recipients with coronary artery disease as compared to the ICD recipients with cardiomyopathy (p = 0.023). Ill. 2, bibl. 6(in English; summaries in English, Russian and Lithuanian).